2021
DOI: 10.3390/molecules26185523
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Antioxidant, Microstructural Properties and Bioaccessibility of Dark Chocolate with Plant Extracts

Abstract: In this study, dark chocolates (DCh) containing zinc lactate (ZnL) were enriched with extracts from elderberries (EFrE), elderflowers (EFlE), and chokeberries (ChFrE) to improve their functional properties. Both dried plant extracts and chocolates were analyzed for antioxidant capacity (AC) using four different analytical methods: 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), cupric ion-reducing antioxidant capacity (CUPRAC), and ferric-reducing antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…These results confirm that EF was a richer source of free and bound phenolics than EB. In our previous study, a water extract from elderflowers also revealed approximately 2.5 times higher TPC (81.9 mg gallic (GA) acid/g) than a water extract from elderberries (TPC = 32.5 mg GA/g) [ 40 ]. Additionally, flowers of different elderberry species or interspecific hybrids (TPC = 7410–40137 μg GA/g) contained significantly higher levels of phenolic compounds compared to berries (TPC = 2687.6–6831.1 μg GA/g) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm that EF was a richer source of free and bound phenolics than EB. In our previous study, a water extract from elderflowers also revealed approximately 2.5 times higher TPC (81.9 mg gallic (GA) acid/g) than a water extract from elderberries (TPC = 32.5 mg GA/g) [ 40 ]. Additionally, flowers of different elderberry species or interspecific hybrids (TPC = 7410–40137 μg GA/g) contained significantly higher levels of phenolic compounds compared to berries (TPC = 2687.6–6831.1 μg GA/g) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, a water extract from elderberries had significantly lower radical scavenging properties of DPPH • (1911.6 μM TE/g) and ABTS •+ (2337.1 μM TE/g) than elderflower extract (DPPH = 4756.0 μM TE/g and ABTS = 6258.7 μM TE/g) [ 40 ]. Moreover, the ABTS values (3.20–39.59 μM TE/g) of various elderberry species and hybrids were considerably lower compared to the ABTS results (44.87–118.26 μM TE/g) of elderberry flowers [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“… The dried plant extract was used for fortification. Poliński et al (2021) Dates and palms To increase the amount of natural sugar extracted from dates and palms and also to reduce the total sucrose content of dark chocolate. The palm and dates were added in the form of syrup.…”
Section: Approaches To Fortify Dark Chocolatementioning
confidence: 99%
“…The highest TPC and antioxidant capacity were observed in dark chocolate enriched with chokeberries (DCh + ChFrE). Viscosity, total fat content and some physiochemical properties (moisture content) were also checked ( Poliński et al, 2021 ).…”
Section: Approaches To Fortify Dark Chocolatementioning
confidence: 99%
See 1 more Smart Citation